Perlindungan Hukum terhadap Korban Salah Tangkap - Fitria, Inayatul; Ahlina, Rusydina Nur (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2024)
Abstract: Law enforcement officials have the right to arrest perpetrators of criminal acts. However, there are still many misdetections due to various factors. In this case, victims of wrongful arrest are entitled to protection. This article discusses legal protection for victims of wrongful arrest in Indonesia. This research is normative juridical research. Data collection was carried out through legal studies and literature analysis, which included books, journals, and articles related to wrongful arrest cases in Indonesia. The data were analyzed descriptively. The results of the study show that victims of wrongful arrest are entitled to legal protection as stipulated in Law Number 8 of 1981 concerning the Criminal Procedure Law. Victims of wrongful arrest are entitled to compensation and rehabilitation. Compensation is given to compensate for losses incurred due to wrongful arrest, while rehabilitation is given to restore the victim's condition. In addition, firm action is needed for law enforcement officers who make false arrests so that there will be no similar incidents in the future. Keywords: Legal protection, victims, mistaken arrest, law. Abstrak: Aparat penegak hukum memiliki hak menangkap pelaku tindak pidana. Namun, masih sering terjadi salah pengkapan karena berbagai faktor. Dalam hal ini, korban salah tangkap berhak mendapat perlindungan. Artikel ini membahas tentang perlindungan hukum terhadap korban salah tangkap di Indonesia. Penelitian ini adalah penelitian yuridis normatif. Pengumpulan data dilakukan melalui  kajian undang-undang serta analisis literatur yang mencakup buku, jurnal, dan artikel terkait kasus salah tangkap di Indonesia. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa Korban salah tangkap berhak mendapat perlindungan hukum sebagaimana diatur dalam Undang-Undang Nomor 8 tahun 1981 tentang Hukum Acara Pidana. Korban salah tangkap berhak mendapat ganti rugi dan rehabilitasi. Ganti rugi diberikan untuk mengganti kerugian yang ditimbulkan akibat salah tangkap sedangkan rehabilitasi diberikan untuk memulihkan kondisi korban. Selain itu dibutuhkan tindakan yang tegas bagi aparat hukum yang melakukan salah tangkap agar tidak ada kejadian yang serupa di masa datang. Kata Kunci: Perlindungan hukum, korban, salah tangkap, undang-undang.